The importance of sleep in selected diseases - Egierska, Dominika Magdalena; Pietruszka, Paulina; Buchta, Justyna (Journal of Education, Health and Sport, 2021)
Introduction: There are specific differences in physiological and biochemical processes during sleep. Adenosine and melatonin are involved in the regulation of circadian rhythms. During sleep, you can observe the secretion of growth hormone, a reduction in cortisol secretion, and a decrease in muscle tone and blood pressure. Sleep can have a major impact on the development of systemic diseases. Aim of the study: A review of the literature aimed at identifying selected negative factors influencing the quality of sleep and systemic diseases which are related to sleep disorders. State of knowledge: Factors that negatively affect sleep include stress, as well as excessive time spent in front of light-emitting screens. Long-term lack of sleep increases the risk of obesity, diabetes, cardiovascular diseases and psychiatric diseases. Summary: Sleep plays an important role in the proper functioning of the body. Its quality is affected by many factors. Sleep disorders can be both the effect and cause of many diseases. Especially in diagnosing psychiatric diseases, attention should be paid to the occurrence of sleep disorders.